Developing students’ reading achievement using PORPE Technique - Nurhadiyanti - (Language and Education Journal, 2021)
The purpose of this study was to examine the application of the PORPE technique in enhancing the eleventh-grade students’ reading achievement of SMAN 3 Unggulan Kayuagung. Since there were five classes with 157 students, the samples were selected using purposive sampling. As a result, there were 62 students who took part as the sample. This study used a quasi-experimental design with nonrandomized pretest and posttest control groups. The data was gathered employing a written test, which was a multiple-choice reading test. The data was analyzed using the t-test. The results revealed that students who were taught through PORPE technique scored higher on reading tests. Besides, PORPE technique could improve the eleventh grade students’ reading achievement of SMAN 3 Unggulan Kayuagung. Hence, students could understand the information form the text and were confidence in answering the questions.